Dietary addition of compound organic acids improves the growth performance, carcass trait, and body health of broilers - Fang Cai; Meiping Huang; Wei Liu; Xiaoling Wan; Kai Qiu; Xiao Xu (Frontiers in Nutrition)
IntroductionThe poultry industry constantly seeks strategies to enhance broiler growth performance and overall health. Organic acidifiers, including L-lactic acid, L-malic acid, and acetic acid, have gained attention as potential feed additives to improve animal production by modulating gut health, enhancing nutrient absorption, and supporting immune function. Despite their promising effects in other animal species, the impact of this novel compound organic acidifier on broiler performance, metabolism, and immune response has not been fully elucidated. This study aims to evaluate the effects of this compound acidifier on growth performance, serum lipid profile, antioxidant status, and immune parameters in broilers, providing insights into its potential benefits as a dietary supplement for broiler health and productivity.MethodsA total of 240 broilers were randomly divided into four groups: a control group and three treatment groups receiving 0.25%, 0.5%, or 1.0% acidifier, with six replicates of ten birds each. Over a 6-week period, various parameters were measured, including serum triglycerides, high-density lipoproteins, lysozyme, immunoglobulins (IgA, IgM), superoxide dismutase (SOD) activity, IL-2, TNF-α, and gene expressions related to lipid metabolism.ResultsOver a 6-week period, the acidifier decreased serum triglycerides and high-density lipoproteins while also enhancing growth performance. Additionally, it raised the serum levels of lysozyme, IgA, IgM, and the SOD. Additionally, IL-2 and TNF-α concentrations in the jejunum mucosa decreased. The acidifier upregulated PPARα, AMPK, FABP1 and MTTP expressions, and downregulated APOB100. Overall, the acidifier effectively improved broiler growth performance during the early development phase primarily by enhancing hepatic lipid metabolism, antioxidant capacity, and immune function.ConclusionThese results suggest that the acidifier may accelerate liver lipid metabolism in broilers by modulating the gene expression profiles involved in lipid metabolism.